(untitled) (Revista de Artes Marciales Asiáticas, 2022)
In judo combat, the grip (kumi-kata) helps to control and to dominate the opponent, and per the current rules is a prerequisite to executing a throwing technique. In this scoping review, articles and reviews published in scientific journals in English were searched in Web of Science, Scopus, PubMed and SPORTDiscus databases from inception until December 2020. The studies were classified into technical-tactical or time-motion analyses, grip or grip attempts, grip locations on uke´s (athlete receiving the attack) judogi (judo uniform) or hands that performed the grips, and one or two hands holding. Articles evaluating the physical and physiological capacities of grip dispute were excluded. From 286 articles identified, 41 were included in the final selection. Two reviewers screened the records independently for eligibility. One reviewer extracted all data and the other reviewed the data for accuracy. The main results showed that: i) more experienced athletes hold the judogi for less time before attacking and focus their vision on the face and collar; ii) male athletes, especially heavy ones, hold longer in the judogi and use more defensive grips (collar and collar); iii) the most used grip was collar and sleeve; iv) the most used position was kenka-yotsu (opposite sides). The result of this scoping review may assist coaches and athletes to develop training strategies according to the athletes’ technical-tactical objectives, as well as future investigations that can be conducted related to grip dispute in judo.